2010
DOI: 10.1016/j.jns.2010.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent polymorphonuclear pleocytosis with increased red blood cells caused by varicella zoster virus infection of the central nervous system

Abstract: We describe an immunocompetent 45-year-old woman who had four episodes of neurological disease (meningoencephalitis, multifocal vasculopathy, myelitis and inflammatory brain stem disease) produced by varicella zoster virus (VZV) over an 11-month period, all in the absence of rash. The cerebrospinal fluid (CSF) contained anti-VZV IgG antibody, but not VZV DNA throughout her illness, reaffirming the superiority of detection of anti-VZV IgG in CSF compared to VZV DNA in diagnosing VZV infection of the nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
4
33
0
3
Order By: Relevance
“…The detection of VZV DNA by PCR or detection of anti-VZV IgG antibody in CSF or both would confirm that VZV produced the neurologic disease. Importantly, the detection of anti-VZV IgG antibody, but not VZV DNA, in the CSF of our patient with VZV encephalitis parallels earlier findings in patients with VZV vasculopathy 6 and VZV myelopathy with brainstem involvement, 9 which showed that the detection of anti-VZV IgG antibody in CSF was superior to that of VZV DNA. More cases of VZV encephalitis need to be studied virologically.…”
Section: Sectionsupporting
confidence: 90%
“…The detection of VZV DNA by PCR or detection of anti-VZV IgG antibody in CSF or both would confirm that VZV produced the neurologic disease. Importantly, the detection of anti-VZV IgG antibody, but not VZV DNA, in the CSF of our patient with VZV encephalitis parallels earlier findings in patients with VZV vasculopathy 6 and VZV myelopathy with brainstem involvement, 9 which showed that the detection of anti-VZV IgG antibody in CSF was superior to that of VZV DNA. More cases of VZV encephalitis need to be studied virologically.…”
Section: Sectionsupporting
confidence: 90%
“…1,7 The presence of neutrophils in early VZV vasculopathy is supported by their abundance in vesicular fluid of zoster patients 13 and in CSF throughout the protracted course of VZV vasculopathy, meningoencephalitis, encephalomyelitis, myelitis, and inflammatory brainstem disease. 9,[14][15][16][17] Although mechanisms of vascular remodeling triggered by VZV are unknown, neutrophils may play a role. When exposed to VZV, they produce reactive oxygen species which mediate smooth muscle cell proliferation and migration 18,19 and induce apoptosis and loss of vascular smooth muscle cells.…”
Section: Figure 3 T-cell Subsets In Varicella-zoster Virus (Vzv) Vascmentioning
confidence: 99%
“…Importantly, many cases of VZV vasculopathy are protracted, and VZV DNA is only found ~30 % of the time [18••]. The detection of anti-VZV IgG antibody in CSF with intrathecal synthesis is superior to detection of VZV DNA in CSF to diagnose VZV vasculopathy [19], recurrent myelopathy, and brainstem encephalitis produced by VZV [29]. …”
Section: Diagnostic Testsmentioning
confidence: 99%